Bahasa Indonesia Bahasa Indonesia - Rinjani Novitasari; Nabila, Fitri; Miharja, Kasmanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to analyze the effect of profitability and company size on audit report lag in telecommunication sector companies for the 2021-2023 period. Researchers used the annual financial statements obtained through the Indonesia Stock Exchange (IDX) during the period concerned in this study. The research method used is quantitative research. Telecommunication sector companies are the object of this research. Researchers conducted several tests in data analysis which included classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study state that variable X1 (Profitability) has a significant effect on variable Y (audit report lag) with a significance value of 0.042 (p <0.05). In addition, variable X2 (company size) also has an influence on variable Y (audit report lag) with a significance value of 0.047 (p < 0.05). And simultaneously, the two X variables affect the audit report lag with a significance value of 0.059. However, this simultaneous effect is not fully convincing at the conventional sig level (5%). This finding indicates that both profitability and company size are important factors that make the length of the audit process (audit report lag) in the telecommunications sector during the study period.